1992
DOI: 10.1007/bf00207043
|View full text |Cite
|
Sign up to set email alerts
|

Allotype distribution of human T cell receptor ? and ? chain genes in Caucasians, Asians and Australian Aborigines: Relevance to chronic hepatitis B

Abstract: RFLPs of TCR beta and gamma genes have been analyzed in chronic HBV carriers of three different ethnic populations to determine if there is an association of TCR allotypes with the development of chronic hepatitis B. The RFLPs of TCR beta and gamma genes were defined respectively by BglII and PvuII genomic fragments on Southern blots. These methods allow allotype assignment. The distribution of TCR beta alleles showed ethnic variation, with one allele significantly decreased in Australian Aborigines, but there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…, 1995). These repertoire changes could lead to a defective immune response, as suggested by Soeharso et al . (1992) in a model of susceptibility to hepatitis B virus infection.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…, 1995). These repertoire changes could lead to a defective immune response, as suggested by Soeharso et al . (1992) in a model of susceptibility to hepatitis B virus infection.…”
Section: Resultsmentioning
confidence: 60%
“…Previous studies have suggested that some germline DNA variants at the TCR locus can modulate the TCR repertoire both qualitatively and quantitatively (Charmley et al , 1993;Posnett et al , 1994;Zhao et al , 1994;De Inocencio et al , 1995). These repertoire changes could lead to a defective immune response, as suggested by Soeharso et al . (1992) in a model of susceptibility to hepatitis B virus infection.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We have shown that the size of peripheral blood T lymphocytes differ significantly between ethnic groups. A report comparing allotype distribution of human TCR chain genes in Caucasians, Asians and Australian Aborigines, found no ethnic variation, but no analysis of total TCR usage was performed [17]. With regard to T-cell TCR V-gene usage, great similarities in different ethnic groups has been shown [18].…”
Section: Discussionmentioning
confidence: 99%